2013
DOI: 10.1080/13548506.2013.811274
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with grief and depression following the loss of a child: A multivariate analysis

Abstract: The present study aims to explore the factors which are associated with grief and depression outcomes in a group of bereaved parents in the first few years following the loss of a child. Sixty-four participants were recruited from bereavement support organisations, between two and 59 months post loss, mean 30 months (SD = 15). They completed a questionnaire packet which comprised standard instruments measuring grief, depression, coping styles, continuing bonds and optimism/pessimism, as well as a number of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
6
27
1
Order By: Relevance
“…In accord with prior research (e.g., Harper et al, 2013), we found that higher optimism was concurrently associated with lower symptom levels of PGD and depression. Our prospective analyses showed that optimism scores did not predict PGD severity 6 and 15 months beyond baseline, when controlling for baseline PGD severity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accord with prior research (e.g., Harper et al, 2013), we found that higher optimism was concurrently associated with lower symptom levels of PGD and depression. Our prospective analyses showed that optimism scores did not predict PGD severity 6 and 15 months beyond baseline, when controlling for baseline PGD severity.…”
Section: Discussionsupporting
confidence: 90%
“…Ai et al (2006) found personal loss in the 9/11 attacks to be associated with more severe posttraumatic stress disorder (PTSD) symptoms among individuals low in dispositional optimism, but not those who scored high on optimism. Harper et al (2013) found optimism to be concurrently associated with less severe complicated grief reactions among parents who lost a child. Wagner et al (2007) examined optimism as an outcome of online therapy for complicated grief; somewhat in contrast with the aforementioned findings, they did not find evidence that baseline optimism was associated with greater reduction in symptoms over time.…”
Section: Introductionmentioning
confidence: 94%
“…Based on the 2011 baseline data from the China Health and Retirement Longitudinal Study 17 whose data cover 17,705 individuals aged 45 or older, living in 10,287 households in 450 rural villages or urban communities with 6,739 observations with complete information, the effects were significantly stronger for losing all the children, similar to losing the only child, than those having a living child or not losing, compared the mental health, happiness and loneliness after adjusting for demographic and socioeconomic characteristics. Previous research also has shown that bereaved parents exhibit more symptoms of depression, anxiety, loneliness, grief, and posttraumatic stress disorder than did their non-bereaved counterparts 18,19 . Meanwhile, bereavement was associated with long-term mortality due to illness (e.g., cancer), presumably because of stress, a weakened immune system, or poor health behaviors (e.g., smoking, alcohol consumption).…”
Section: The Difference Between Sdp and Other Bereavementmentioning
confidence: 91%
“…This is supported by bereavement literature concerning parental responses to the loss of their child (e.g. Harper, O'Connor, & O'Carroll, 2013). The mothers were interviewed after their child completed treatment with a successful outcome.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%